Crimes against road safety: critical view of the Spanish regulation - Polaino-Orts, Miguel (2021)
Criminal law on road safety has received growing attention from criminal law doctrine in recent years, largely due to the profound and successive legal reforms to which it has been subjected. In the last three decades, Spanish criminal legislation has undergone a wide modification in these crimes, introducing new figures and substantially reforming old figures, in addition to aggravating the criminal justice system. Most of these crimes punish an anomalous or incorrect driving, which is either really unsafe (that is, it creates insecurity in road traffic), or it is presumed that it is. Along with them, there are two other heterogeneous figures related to road traffic: on the one hand, the crime of refusal by the driver to submit to a breathalyzer or drug addiction control; on the other, the creation of a serious risk to traffic through certain behaviors, precisely the development of these figures will constitute the central axis of this article. It should be noted that general provisions are contained in this headquarters.